Biomechanical analysis of a short femoral stem used in revision total hip replacement of a standard femoral stem - Shuang G. Yan; Zhi Wang; Yiliang Cui; Fanxiao Liu; Jingtao Lu; Hui Zhang; Di Li (Scientific Reports)
Abstract Short-stem total hip arthroplasty (SHA) has become popular because it preserves femoral bone stock and enables the use of short femoral stems in revision total hip arthroplasty (THA). However, no study has evaluated whether a short stem in revision THA, replacing a standard stem, can provide adequate primary stability to facilitate osseous integration. In this biomechanical study, a metaphyseal anchoring SHA (Tri-Lock BPS) stem and a standard THA (Corail) stem were implanted into ten composite femurs and loaded dynamically from 300 to 1700 N with 1 Hz. Primary stability was estimated using three-dimensional (3D) micromotions at five points around the bone–implant interface. A revision scenario was then established by removing the standard stem and implanting the same Tri-Lock BPS stem, with subsequent measurements of 3D micromotions. In the primary scenario, no significant differences in 3D micromotions were noted between the short and standard stems at most of the test points. Compared with the Corail group, the Tri-Lock BPS group presented significantly greater 3D micromotions only at the lateral point of the distal femur (P5: Tri-Lock BPS 32.9 ± 7.54 μm vs. Corail 25.1 ± 4.32 μm; p = 0.011). In the revision scenario, no significant differences in the 3D micromotions were noted between the primary and revision Tri-Lock BPS stems at all test points. Our results show that the SHA (Tri-Lock BPS) offers good primary stability, which is similar to that of the standard THA (Corail). The Tri-Lock BPS stem obtained comparable stability in this revision scenario as in the primary scenario; therefore, it can be assumed that the Corail standard stem can safely be revised with a Tri-Lock BPS short stem.